Strategic change in resolving the efficiency-equity dilemma: A novel approach to portfolio selection - Azmi, R. A.; Salloum, C.; Pereira, R.; Jarrar, H.; Verdie, J.‐F. (Strategic Change, 2025)
This paper introduces an innovative portfolio selection methodology that incorporates extended goal programming (EGP) to address the efficiency-equity tradeoff in international portfolio management. Unlike traditional methods, EGP integrates multiple-objective optimization, allowing for a balanced consideration of risk, return, and correlation simultaneously. This study not only advances the theoretical framework of portfolio management by extending the principles of Modern Portfolio Theory (MPT) but also provides empirical evidence of EGP's robustness across various market conditions, including financial crises. Utilizing data from five major global stock markets, which collectively represent over 70% of global market value, the results demonstrate that EGP-constructed portfolios outperform both global and market-specific benchmarks. The research contributes to the literature by offering a flexible, adaptable tool for decision-makers, enabling them to tailor portfolio strategies to diverse investor goals and volatile market environments. This study's findings have significant implications for both academics and practitioners, paving the way for more resilient and optimized portfolio management practices.